Simulation of Root-Matted Cutting by Use of Distinct Elemet Method - Bambang Purwantana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
A numerical technique, the distinct element method (DEM.l, was used to simulate the mechanical behavior of root-matted soil. The conventional DEM was modified with introducing a tensile parameter on the mechanical relationship between the DEM elements. The validity of the modified model was investigated by conducting an experiment in which root-matted soil is cut by a blade. The simulation results indicate the appropriateness of the modified DEM The effects of tension from the experimental results could be simulated by the DEM. This study has provided new and valuable information on the behavior of soil and root at cutting process.